CORPORATE SOCIAL RESPONSIBILITY, DIVIDEND POLICY AND NUMBER OF INDEPENDENT COMMISSIONERS - MUHTAROM, ABID; WARDANI, LINA KUSUMA; GHOFUR, ABDUL; NURINDYAH, ANGELINA AGNES (The journal of contemporary issues in business and government, 2021)
Dividend policy of a company is an important information for shareholders and prospective shareholders. Dividends distributed by the company is a positive signal, because the company is considered profitable in its business. Dividend policy taken is influenced by CSR. CSR programs have a positive influence on the company but these activities can cause agency problems between company managers and shareholders. With the emergence of agency problems, companies must look for outsiders to help reduce agency problems, namely the emergence of independent commissioners in the organizational structure. The independent commissioner functions to provide advice and control the activities of the company manager. This study aims to examine and analyze the relationship between corporate CSR with dividend policy taken by the company, later the relationship of CSR with dividend policy is moderated by the percentage of the number of independent commissioners. The sample used is non-financial companies listed on the Stock Exchange in the 2015-2019 period. The method used was purposive sampling involving 235 observations. Research analysis techniques are multiple linear regression analysis and multiple linear regression analysis with moderation. The results of this study are that there is no significant relationship between corporate CSR with dividend policy, then the percentage of the number of independent commissioners cannot strengthen the relationship between CSR and dividend policy, but the percentage of the number of independent commissioners has a significant negative effect on dividend policy. In this study also found that the size and growth of the company does not affect dividend policy. Then for leverage and profitability the company has a significant positive relationship to the company’s dividend policy.